Exploring research trends and hotspots in PI3K/Akt signaling pathway in ischemic stroke: a bibliometric analysis - Liu, Yingquan; Ye, Yu; Bai, Lin; Dai, Fan; Su, Xingxing; Hu, Peijia; Cheng, Hongliang (Frontiers in Molecular Neuroscience, 2025)
ObjectiveThis study explores potential therapeutic strategies by determining the current research status, hotspots, and development trends through bibliometric analysis of the PI3K/Akt in ischemic stroke (IS).MethodsWe searched the Web of Science Core Collection for publications on IS and the PI3K/Akt pathway, covering January 1, 2010, to December 31, 2024. VOSviewer and CiteSpace software were used to analyze research hotspots and cutting-edge topics in the field and generate visual maps of relevant countries, institutions, authors, journals, keywords, and references.ResultsA total of 635 publications were analyzed. The number of publications indicates a steady annual increase in research output. China, Capital Medical University, and Wang Lei were identified as the most prolific country, institution, and author, respectively. The top three contributing journals were Brain Research, Journal of Ethnopharmacology, and Frontiers in Pharmacology. Autophagy, microglia and neuroinflammation, bioinformatics approaches, and traditional Chinese medicine (TCM) are not only current research areas but also important trends for future research. Notably, targeting IS with TCM holds significant potential for translating basic research findings into clinical applications.ConclusionThis bibliometric analysis provides an in-depth overview of research on the PI3K/Akt pathway in IS, revealing current research status, hotspots, and future research trends. This will provide valuable guidance and direction for developing novel therapeutic strategies targeting this pathway.